1990
DOI: 10.1007/bf00117789
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of metastasis in a murine mammary tumour model by heparin and polyinosinic-polycytidylic acid

Abstract: A murine mammary tumour model has been used to test the efficacy of a combination of heparin and the interferon inducer, poly I:C on spontaneous metastasis from a s.c. primary tumour and on experimental metastasis following i.v. injection of tumour cells. This treatment has no effect on the growth of primary tumours, but lung metastases arising from these tumours were reduced. When tumour cells were injected i.v. the number of lung colonies was significantly reduced and survival time extended. Short-term treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…This is likely to be due to a direct effect of heparin on the metastatic process as a number of experimental studies have confirmed that cancer progression can be influenced by heparins [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to be due to a direct effect of heparin on the metastatic process as a number of experimental studies have confirmed that cancer progression can be influenced by heparins [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Heparins were repeatedly shown to effect cancer progression, while their effect on tumor growth was rather limited [16,20,21]. Over the last twenty years, the antimetastatic activity of heparins was primarily observed in animal models of experimental metastasis (Table 1).…”
Section: Heparin Attenuates Metastasis In Animal Modelsmentioning
confidence: 99%
“…Intravenous application of heparin around the time of tumor cell injection always led to reduction of metastasis. Subcutaneous or intraperitoneal application of heparin around the time of tumor cell injection led mostly to attenuation of metastasis [11,14,20,[25][26][27], while in some studies the affectivity of heparin was limited [17,[28][29][30]. Attenuation of metastasis was repeatedly observed in most of the studies despite a wide range of heparin dosages applied (Table 1).…”
Section: Heparin Attenuates Metastasis In Animal Modelsmentioning
confidence: 99%
“…The direct effect of anticoagulants on the ability of platelets to regulate angiogenesis and tumorigenesis has not been determined. [30][31][32][33][34][35][36][37][38] In most preclinical studies, the anticancer effects of LMWH and UFH did not affect the primary tumor directly, but rather reflected interference in the metastatic pathway. The publication costs of this article were defrayed in part by page charge payment.…”
Section: Introductionmentioning
confidence: 99%